Design and comfort in office space - Michele M. Lepore (Vitruvio: International Journal of Architectural Technology and Sustainability, 2017)
The theme of office space is of particular interest because it is a sector strongly involved by technological development. The high concentration of plant engineering systems makes it essential to the attention to environmental parameters and to research on the quality of the relationship which binds man to artificial dimension of built space. In the design of office spaces, the general objective must be to be able to achieve a new working environment relationship. A ratio in which optimal balance is always sought in terms of igrothermal, acoustic and luminous comfort conditions, without noting that the psychological and sociological component plays an important role among the environmental factors, and this significantly interferes with the conditions of physiological comfort. The following work is an essay on the subject.